2016
DOI: 10.1111/jfpp.12759
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated Rosemary (Rosmarinus officinalis) Essential Oil as a Biopreservative in Minas Frescal Cheese

Abstract: The objective of this study was to evaluate the effect of rosemary essential oil encapsulation using whey protein isolate (WPI) and inulin as encapsulation matrix on the shelf‐life extension of Minas frescal cheese. Essential oil in bulk and microencapsulated forms were added to cheese at concentrations of 0.5% and compared with control treatment (cheese without rosemary essential oil). The aerobic mesophilic microorganism counting cheese with added microencapsulated rosemary essential oil was lesser than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 45 publications
(56 reference statements)
1
32
0
1
Order By: Relevance
“…In both cases these loaded films were more effective (2-3 logs reduction) against mesophilic bacteria than for L. monocytogenes or S. aureus strains. Although several research works have reported the antimicrobial potential of EOs for extending the shelf life of different food products (Oussalah et al, 2004, Fernandes et al, 2017, Ahmed, Hiremath, & Jacob., 2016, a greater effect was found for the 10% LEO loaded NFbased coating, in which a bactericidal effect on undesired spoilage microorganisms for cheese was observed at the end of the storage period. A possible explanation for this would be related to a more sustained release of the bioactive compounds when the essential oil was nanoencapsulated…”
Section: Challenge Testmentioning
confidence: 99%
“…In both cases these loaded films were more effective (2-3 logs reduction) against mesophilic bacteria than for L. monocytogenes or S. aureus strains. Although several research works have reported the antimicrobial potential of EOs for extending the shelf life of different food products (Oussalah et al, 2004, Fernandes et al, 2017, Ahmed, Hiremath, & Jacob., 2016, a greater effect was found for the 10% LEO loaded NFbased coating, in which a bactericidal effect on undesired spoilage microorganisms for cheese was observed at the end of the storage period. A possible explanation for this would be related to a more sustained release of the bioactive compounds when the essential oil was nanoencapsulated…”
Section: Challenge Testmentioning
confidence: 99%
“…Campelo et al () stated that the encapsulation efficiency of lime essential oil microencapsulated into MD and whey protein was about 83%. These results showed that their encapsulation efficiency is lower than encapsulation efficiency obtained for the cinnamon essential oil microparticles in this study; the difference in encapsulation efficiency can be due to the variety of wall material and purity of essential oil encapsulated (Fernandes et al, ).…”
Section: Resultsmentioning
confidence: 58%
“…The nature of the barrier material is one of the significant attributes in the holding of volatile oils (de Barros Fernandes et al, ). GA is the most common and broadly applied component for entrapment volatiles due to its emulsifying characteristics and excellent retention of essential oils during spray‐drying (Fernandes et al, ). Nevertheless, this compound has limited access and a high cost.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic activity in foodstuffs result in some chemical reactions leading to food spoilage, thus making foods inedible or decreasing their qualities [91,92]. In addition to being an important health issue, which may sometimes lead to death, it may also yield great economic losses [93]. The World Health Organization reported that unsafe food resulted in illnesses in approximately two billion people throughout the world, and some of the cases were actually fatal [94].…”
Section: Food Applications Of Veronica Plants and Other Usesmentioning
confidence: 99%